Rating gender stereotype violations: The effects of personality and politics - Hammond-Thrasher, Stephanie; Järvikivi, Juhani (Frontiers in Communication, 2023)
The Gender Stereotype Effect in language comprehension refers to the increased processing load that occurs when comprehenders encounter linguistic information that is incongruent with their understanding of gender stereotypes; for example, upon encountering the pronoun he in the sentence The maid answered the phone because he heard it ring. We investigate the Stereotype Effect using appropriateness and correctness ratings and ask whether it is modulated by individual differences in participants' personality and political ideology. Results from this study indicate that the Stereotype Effect can be replicated in an offline paradigm and that the Effect is gender specific: sentences describing male agents fulfilling stereotypical female roles are rated lower than sentences describing female agents fulfilling stereotypical male roles. Further, more open, conscientious, liberal, and empathetic individuals were more sensitive to the gender-specific effect, rating stereotype incongruent sentences, particularly female role-male pronoun pairings, lower than congruent ones . Overall, these results point to the fact that certain individual differences are associated with top-down language processing, where comprehenders might make more use of extra-linguistic, sociocultural factors in their sentence comprehension. Additionally, the results indicate a gender-based difference in sociocultural stereotypes.